ADAPTATION OF SPORTS AND LEISURE COMPLEXES NETWORK IN UKRAINIAN CITIES TO CLIMATE CHANGE (MODERN CONSTRUCTION AND ARCHITECTURE, 2023)
The climate change that is taking place all around the world today presents challenges for all inhabitants of the planet, including the citizens of Ukraine. Taking all of these circumstances into consideration, it is necessary to introduce new methods of forming the environment that meet the new conditions. The article examines the influence of climate change on the recreational spaces of Ukrainian cities focusing on the location of sports and leisure complexes and their facilities. The article explores the influence of the temperature and humidity of the recreational environment on the athletes' performance and health.The work identifies and systematizes the positive and negative effects of the climate change on a network of sports and leisure complexes and their athletes. The main implication is that outdoor activities can cause heat stress during periods of high ambient temperature. This indicates that the existing sports and leisure complexes are not adapted to climate change. The paper studies the world's practical ways of adapting the urban environment to climate change paying particular attention to a system for alerting the population about the heat waves and informing the citizens about ways to strengthen their immunity; the creation of green and water infrastructure in cities and suburban areas; systems for objective monitoring of diseases and infectious agents affected by climate change, as well as planning for the prevention of these diseases; ensuring the population's access to clean drinking water and monitoring compliance with the technology of disinfection and purification. The study, premised on this analysis, has provided several proposals for adaptive measures implemented while designing a network of sports and leisure complexes in the architectural and urban planning aspects. It is predicted that such measures will help visitors adapt to climate change.It enables us to develop approaches for forming a future network of sports and leisure, taking into consideration cities' changing climatic conditions.
Keywords: Ukrainian cities; climate change; athlete's performance; climate adaptation; the network; sport and leisure complex.